Porovnání klinických výsledků léčení dislokovaných zlomenin diafýzy klíční kosti - Klézl, Zdeněk; Marvan, Jiří; Ježek, Jakub; Douša, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY The aim of this retrospective study was to assess the subjective evaluation of treatment by patients with respect to their return to work and recreational sport following the fracture of clavicle diaphysis with posttraumatic shortening of 1.5 cm, or more, treated non-operatively and surgically. MATERIAL AND METHODS Our group of patients consisted of 51 patients (14 females, 37 males) aged between 18 and 89 years (average age 46 years). We concentrated on the parameters of sex, age, side of injury, extent of posttraumatic shortening, method of treatment, return to work or recreational sport, DASH score at one year post non-operative or surgical treatment. Patients who sustained a pathological fracture, fractures of the clavicle combined with an injury of the acromioclavicular joint or simultaneous fracture of the humerus or the ribs were excluded from the study. Patients with open fractures or re-fractures were excluded as well. The indication for treatment selection was based on pre-operative discussion of the doctor with the patient and the Informed Consent was signed. The patient was informed about different treatment options. A shorter period of fixation of the arm and post-operative physiotherapy was mentioned in connection with surgical treatment as well as potential surgical complications. A statistical analysis comparing the data in both groups was conducted using the Fisher exact test. The p-value of 0.05 or less was considered as statistically significant. RESULTS The right side was affected 26 times, the left side 25 times. The shortening ranged from 1.5 to 3.7 cm. 24 patients (8 females, 16 males) aged 21 to 89 years (average 54 years) were treated non-operatively. 27 patients (6 females, 21 males) aged 18 to 74 years (average 38 years) underwent surgery. The difference in sex distribution in both groups was not statistically significant (p = 0.5311). According to the Robinson classification, there were 17 patients with type 2A2 fractures, of whom 8 underwent surgery and 9 were treated non-operatively, 19 patients with type 2B1 fractures, of whom 9 underwent surgery and 10 were treated non-operatively, and 15 patients with type 2B2, of whom 10 underwent surgery and 5 were treated non-operatively. The surgically treated patients prevailed in type 2B2 only, but this difference was not statistically significant (p = 0.2350). In the non-operatively treated group, 23 out of 24 patients returned to pre-injury activities in 3 months on average. Ten patients (48%) reported reaching the same function as on the other side. In the DASH score evaluation, 11 patients reached the value of 0-3.3, five patients 3.4-10, six patients 10.1-30.0 and two reached the score of more than 30. In the evaluation of capacity to work, 15 out of 24 patients were able to work, 11 of them without any restrictions or difficulties. In the evaluation of the sport and playing musical instrument module, 9 out of 24 patients did not engage in sports activities or do not play any musical instruments. In the surgically treated group, 26 out of 27 patients returned to pre-injury activities within 6 weeks. 19 (70%) patients reported reaching the same function as on the other side. In the DASH score evaluation, 19 patients reached the value of 0-3.3, two patients 3.4-10, 5 patients 10.1-30.0 and one patient with nonunion 72.5. Comparison of the average values of the DASH score demonstrated slightly better results achieved by surgical treatment (9.03 vs 6.77). When assessing the work module, 24 out of 27 patients returned to work, 20 of them without any restrictions or difficulties. Out of 27 patients, 4 patients were no longer able to engage in sports activities or to play a musical instrument. Of the 23 remaining patients, 18 did not have any problems, 5 suffered from minimal problems. The group of patients treated non-operatively included one case of non-union and the same applies to the surgically treated group. In 3 patients the removal of hardware was performed, 3 patients underwent revision of the surgical wound because of infection. DISCUSSION The recommendation of the weight-bearing of the upper extremity was similar in both groups, 12 weeks post injury/surgery on average. It is clear that sooner return to work or sports activities in the surgically treated group was preferred by younger patients who expected quicker recovery. Younger patients were less patient and more eager to return to work and sports, while the older patients, on the other hand, were more cautious about possible complications of surgery. CONCLUSIONS The results of our study did not identify any correlation between the clavicle shortening and the indication for surgical treatment. Surgical treatment was preferred by younger patients, more frequently by males. The rationale was supported by the perspective of sooner return to work and favourite sports activities. Their decision was not affected by the known risks of surgical treatment. Evaluation of the DASH score at one year after injury/surgery showed similar results. A higher incidence of complications in the surgically treated group did not lead to negative evaluation of the selected treatment modality by the highly motivated group of patients either. Key words: fractures of the clavicle diaphysis, non-operative treatment, surgical treatment, return to work, return to sports activities, functional results at 1 year.
Keywords: senioři; senioři nad 80 let; klíční kost; diafýzy; Retrospective Studies; mladiství; výsledek terapie; Middle Aged; mužské pohlaví; Fracture Fixation, Internal; Diaphyses; Adult; mladý dospělý; Fractures, Bone; sporty; Aged, 80 and over; Young Adult; ženské pohlaví; Clavicle; retrospektivní studie; Humans; fraktury kostí; vnitřní fixace fraktury; lidé středního věku; dospělí; Sports; Female; Aged; Adolescent; Treatment Outcome; lidé; Male